The Role of Motivation in Mediating the Influence of Leadership, Technology Use, and Work Discipline on Employee Performance - Raka, Anak Agung Gede; Martini, Ida Ayu Oka (Quantitative Economics and Management Studies, 2024)
This think about explores the part of inspiration in interceding the impact of administration, technology usage, and work discipline on employee performance. The research employs quantitative data collected from 58 employees at the Abiansemal District Office using a questionnaire. The data analysis was conducted using multiple linear regression with the PLS program. The comes about uncover that authority and innovation utilization emphatically influence representative execution, whereas work teach does not have a critical coordinate affect. However, inspiration is found to intercede the relationship between authority, innovation utilization, and worker execution. The findings of this study suggest that enhancing motivation can strengthen the positive effects of leadership and technology usage on performance, indicating the importance of motivational strategies in organizational management. These insights emphasize the necessity for managers to focus on creating a motivating work environment that supports effective leadership and the adoption of advanced technologies to drive employee performance and overall organizational success. This approach can lead to sustainable improvements and foster a culture of continuous development and innovation.